MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MEDIA KOMPUTER DAN PROJEKTOR LCD PADA POKOK BAHASAN DIMENSI TIGA - Herlina Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2016)
This research is a classroom action research carried out during two cycles, which aims to increase the students' mathematics learning class X4 through programming Microsoft Power Point into computer media and projector LCD on the subject of three dimensions in SMA 8 Makassar. The subjects were students of class 8 Makassar X4 SMU taught by the author as many as 36 students. Data collection through achievement test after completion of material taught at the end of each cycle. The data analysis technique is qualitative and quantitative, quantitative analysis using descriptive statistical results of this study indicate that: (1) An increase in the results of students' mathematics learning of the first cycle keSiklus II after improvement slide on programming Microsoft Power Point (MPP) into computer media and LCD projector. (2) the first cycle students 'average score of 57.80 with a standard deviation of 10.14 at the ideal score of 100. (3) Cycle II students' average score of 78.33 with a standard deviation of 9.85 to the ideal score of 100. (4) the presence, liveliness and sincerity students attend learning activities also showed an increase visible from the observation during the learning takes place. Based on these results it can be concluded. Whereas, the application of the use of computer media and LCD projectors with learning programs that are made of a presentation application program that Microsoft Power Point (MPP) students may be interested and motivated to participate in learning activities that increase math learning outcomes.